Azumanga daioh [videorecording (DVD)] : the animation : complete collection - Azuma, Kiyohiko (Sentai selects., 2016)
For the members of Miss Yukari's English Class, a typical day may be just a little unusual. Part of that's due to Miss Yukari herself, whose teaching style (and personal ethics) tend to be odd, improvisational and spontaneous, but her students are just as unconventional: They may all seem like perfectly normal girls on the outside, but even their most mundane activities magically become the most extraordinary adventures as they learn all about life, the universe and affairs of the heart.